Analytic versus systemic group therapy for women with a history of child sexual abuse: 1‐Year follow‐up of a randomized controlled trial. (7th September 2013) - Elkjaer, Henriette; Kristensen, Ellids; Mortensen, Erik L.; Poulsen, Stig; Lau, Marianne
<x xml:space="preserve">Abstract</x> Objective This randomized prospective study examines durability of improvement in general symptomatology, psychosocial functioning and interpersonal problems, and compares the long‐term efficacy of analytic and systemic group psychotherapy in women 1 year after completion of treatment for childhood sexual abuse. Design and Methods Women (n = 106) randomly assigned to analytic or systemic psychotherapy completed the Symptom Checklist‐90‐R, Global Assessment of Functioning, Global Life Quality, Registration Chart Questionnaire, and Flashback Registration at pre‐treatment, post‐treatment, and at a 1‐year follow‐up. Results Post‐treatment gains were significant for both treatment modalities on all measures, but significantly larger after systemic therapy. Significant treatment response was maintained 1‐year post‐treatment, but different trajectories were observed: 1 year after treatment completion, improvements for analytic therapy were maintained, whereas they decreased after systemic therapy, resulting in no statistically significant difference in gains between the groups at the 1‐year follow‐up. Despite maintaining significant gains, more than half of the patients remained above cut‐off for caseness concerning general symptomatology at post‐treatment and at 1‐year follow‐up. Conclusion The findings stress the importance of long‐term follow‐up data in effect studies. Different trajectories were associated with the two treatments, but improvement in the two treatment groups did not differ significantly at the 1‐year follow‐up. Implications of the difference in trajectories for treatment planning are discussed. Practitioner points Both analytic and systemic group therapy proved efficient in improving general symptomatology, psychosocial functioning, and interpersonal problems in women with a history of CSA and gains were maintained at a 1‐year follow‐up. Despite maintaining statistically significant gains at the 1‐year follow‐up, 54% of the patients remained above the cut‐off for caseness with respect to general symptomatology, which may indicate a need for further treatment. Different pre‐post follow‐up treatment trajectories were observed between the two treatment modalities. Thus, while systemic group therapy showed a significantly better outcome immediately after termination, gains in the systemic treatment group decreased during follow‐up, while gains were maintained during follow‐up in analytic group therapy.